Notes on the Tadpoles and Breeding Ecology of Lepidobatrachus (Amphibia: Ceratophryidae) - Cei, José Miguel Alfredo María (1968)
Lepidobatrachus is a characteristic Chacoan genus of the Ceratophryidae, which we consider to be an independent Neotropical phyletic line of leptodactylids. Its earliest known representative is the Miocene Wawelia from Patagonia (Casamiquela, 1963). Since the discovery of the genus by Budgett (1899), Lepidobatrachus has received relatively little comment. Vellard (1948) redescribed the type-species, and the generic status has been confirmed by Cei (1958), Reig and Cei (1963), and Barrio (1967) utilizing various lines of investigation. The latter author proposes recognizing three species: L. laevis Budgett, L. asper Budgett (L. salinicola Reig and Cei is a synonym), and L. llanensis Reig and Cei, whose distributions are largely allopatric but in part sympatric (Fig. 1). Except for Parker’s (1931) brief description and figures of the tadpole of Lepidobatrachus asper (= either asper or laevis by current concepts), the larvae of the genus have not been described. The tadpoles of L. asper and L. llanensis are described and figured in this paper. These species occur in the shrub-covered flats of the Argentine Central and Western Chacoan provinces. These Chacoan frogs are characterized by a clear-cut seasonal rhythm which is correlated with the wet summers and dry winters of the semi-arid regions in which they live. During the cold dry season, they remain underground, not feeding or moulting. Mating and egg-laying occur during the rainy season (October to February). Breeding activity usually takes place in the temporary roadside pools on clay soil. The small, pigmented eggs lie on the muddy bottom. Early cleavage and development remain unknown. After hatching, individual tadpoles in various developmental stages are found swimming in the shallow parts of temporary pools. Tadpoles of L. llanensis were collected in La Rioja Llanos, near Oita (Rio Colorado), Chepes, Punta de los Llanos and Chamical, Argentina, 300-400 m in elevation. Tadpoles of L. asper were collected in the salt flats of Salares de Santiago del Estero, Argentina. All are preserved at the Instituto de Biologia, Universidad Nacional de Cuyo, Mendoza, Argentina (IBM-UNC), and form the basis for the following descriptions.